The effects of doxycycline and micronized purified flavonoid fraction on human vein wall remodeling are not hypoxia-inducible factor pathway-dependent. - Lim, C; Kiriakidis, S; Paleolog, E; Davies, A (2012)
BACKGROUND: Doxycycline and micronized purified flavonoid fraction (MPFF) modulate vein wall remodeling that may be associated with hypoxia in varicose veins (VVs), vein graft stenosis, and deep venous thrombosis. We recently reported that in vitro exposure of non-VV (NVVs) and VVs to hypoxic conditions activates the hypoxia-inducible factor (HIF) pathway. This study investigated the in vitro effects of doxycycline and MPFF on the HIF pathway in hypoxic NVVs and VVs. METHODS: Six NVVs and six VVs obtained from surgery were used to prepare vein organ cultures, which were exposed to hypoxia (1% O(2)), with and without MPFF (10(-5) mol/L) or doxycycline (5 μg/mL) for 16 hours. The veins were analyzed for HIF-1α, HIF-2α, and their target gene expression, with real-time polymerase chain reaction and Western blot. The differences between gene expressions were tested with one-way analysis of variance with repeated measures, followed by the Dunnett test for multiple comparisons. P < .05 was considered significant. RESULTS: Treatment of NVV organ cultures exposed to hypoxia with doxycycline or MPFF did not significantly alter the expression of HIF-1α and HIF-2α messenger (m)RNA and protein compared with untreated. Doxycycline also did not significantly affect the expression of HIF-1α and HIF-2α mRNA and protein in VVs exposed to hypoxia compared with untreated VVs. However, MPFF significantly reduced the expression of HIF-1α but not HIF-2α mRNA in VVs exposed to hypoxia compared with untreated VVs. Interestingly, the reduction of the expression of HIF-1α mRNA in VVs by MPFF was not reflected at the protein level. The mRNA expression of HIF target genes, namely glucose transporter-1, carbonic anhydrase-9, vascular endothelial growth factor, B-cell lymphoma 2/adenovirus E1B 19-kDa protein-interacting protein 3, prolyl hydroxylase domain-2, and prolyl hydroxylase domain-3, was not significantly altered in NVVs and VVs exposed to hypoxia and treated with doxycycline or MPFF compared with those untreated. CONCLUSIONS: Doxycycline and MPFF at a concentration corresponding to a therapeutic dose do not alter the activation of the HIF pathway in NVV and VV organ cultures exposed to hypoxia. Our findings suggest vein wall remodeling actions in NVVs and VVs are likely not HIF-dependent.